Elucidation of the Adsorption/Desorption Mechanism of Ions by an Electrical Double Layer Capacitor - H. Oda; K. Mizutaki; M. Yamamoto; M. Sano (Adsorption Science & Technology)
The phenomena associated with the adsorption/desorption of ammonium, nitrate and phosphate ions by an electrical double layer capacitor (EDLC) were examined as a new application of this device for the removal of environmental pollutants from freshwater rivers, lakes and marshes. An electrode modified by introducing acidic functional groups onto its surface was used as the negative electrode of an EDLC, and this resulted in a 1.7-times increase in the amount of ammonium ions removed compared with that of an unmodified electrode. However, when the quantity of functional groups was increased to over 1.5 mmol/g, the amount of ammonium ions removed gradually decreased due to steric hindrance of the functional groups on the surface of the electrode and/or redox reactions with these groups. Similarly, it was found that the EDLC easily adsorbed nitrate ions but did not easily desorb them, whereas the opposite was the case for phosphate ions. The relationship between these phenomena and the pH pzc (pH value at the point of zero charge) of the electrode in nitrate and phosphate solutions is presented.